Cystic Fibrosis in Asia - Shakil Ahmed; Gary Cheok; Anne EN Goh; Aye Han; SJ Hong; Wahyuni Indawati; ARM Lutful Kabir; S K Kabra; Harutai Kamalaporn; Hyung Young Kim; Shen Kunling; Sorasak Lochindarat; et al. (Pediatric Respirology and Critical Care Medicine)
Background: Cystic fibrosis (CF) is the most common inherited life-limiting illness in the Caucasian population. It is considered to be rare in Asia, but recent reports suggest that CF does occur in Asia. Methods: We carried out a questionnaire-based survey to determine the prevalence of CF across Asian countries and the diagnostic and therapeutic capabilities available in member countries. A questionnaire was sent to member countries of the Asian Pediatric Pulmonology Society. The questionnaire included the total number of children diagnosed with CF seen in the country and the available resources. available resources for diagnosis and management. Results: Fifteen countries responded to the questionnaire. Three countries/regions (Myanmar, Vietnam, and Macau) have not recorded any case of CF. The remaining 12 countries have recorded a variable number of cases which have also been reported in the literature. Sweat chloride testing facilities were available in all the countries except Taiwan that reported cases of CF. Some countries such as India and Bangladesh have developed their own indigenous method for sweat testing. Some countries have facilities for mutation testing. Basic medications such as pancreatic enzyme supplementation and antibiotics were available in all the countries where children with CF have been diagnosed. Inhaled antibiotics and dornase alfa were available only in a few countries. Some other countries reported using the injectable preparation of gentamicin and amikacin for inhalation therapy. Testing for genetic mutation wherever available showed a low frequency of the Delta F 508 mutation which is the most common mutation found in the Caucasian population. Only two countries (India and Japan) have formal CF associations for the affected community. Two countries Japan and China maintain a CF registry, whereas India already started the process of developing it. Conclusion: CF is increasingly being diagnosed over the past two decades in Asian countries. There is a need to create awareness among pediatricians and to develop regional or country-specific protocols and tools for the diagnosis and treatment of children with CF.